Sorting things out : classification and its consequences. - Bowker, Geoffrey C. (Inside technology., 2000)
"In Sorting Things Out, Geoffrey C. Bowker and Susan Leigh Star explore the role of categories and standards in shaping the modern world. They investigate a variety of classification systems, including the International Classification of Diseases, the Nursing Interventions Classification, race classification under apartheid in South Africa, and the classification of viruses and of tuberculosis."--BOOK JACKET.